Studi Karakteristik Dan Potensi Pengolahan Sampah Di Kampus Bina Widya Universitas Riau - Wulandari Wulandari; Lita Darmayanti; Jecky Asmura (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Solid waste is one of the environmental problems linked to our lives. University of Riau (UR) is a public university in Pekanbaru that can not be separated from the solid waste problems in which there is currently do not have alternative solid waste treatment. The purpose of this study was to determine the potential of treatment and economic potential. Method sample in campus 8 days consecutive shows, with location of sample solid waste faculty, office, canteen, hospital, road, and mosque. Analysis sample characteristic of proximate (water content, volatil, ash and fixed carbon) and garbage energy by using appliance bomb calorimeter. The percentage of the proximate analysis recapitulation waste mixed conditions the average percentage generated of 43,5% water content, volatile content of 45,7%, ash content of 2,2% and fixed carbon of 6,8%. Percentage recapitulation waste proximate analysis by components highest water content of 37,9% of organic waste, volatile content of 83,8% textile waste, ash content of 26,2% plastic waste, and fixed carbon of 96,8% waste iron. The highest calorific value waste is plastic waste that of 12671.56 cal/gr. Solid waste that has economic potential sale value to collectors obtained for Rp.107.735,-/day. Mass balance of weight solid waste with a daily average weight of 816 kg/day, which can be utilized 512 kg/day and the weight of solid waste being dumped into temporary disposal location 303 kg/day. Solid waste treatment for organic waste such as composting or animal feed, while the inorganic waste can be recycled and waste that has economic value can be sold directly to collectors, while the waste that is not used will be disposed to landfill the city of Pekanbaru.Keywords: characteristics, treatment, solid waste, campus, UR.